1983
DOI: 10.1172/jci111046
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone suppression with dopamine infusion in low-renin hypertension.

Abstract: A B S T R A C T A dopaminergic mechanism has been proposed to suppress aldosterone secretion. To assess the possibility that a defect in the dopaminergic mechanism might enhance aldosterone secretion in hypertensive patients, we determined basal and adrenocorticotropic hormone (ACTH)-stimulated plasma aldosterone (PA), cortisol, renin activity, and potassium concentrations before and during dopamine receptor stimulation with dopamine infusion and bromocriptine administration and dopamine receptor blockade with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1984
1984
1991
1991

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Plasma potassium determinations were also somewhat suggestive that these patients had subtle primary aldosteronism in that most of these patients had borderline hypokalemia. In addition, some of these patients demonstrated an enhanced aldosterone response to ACTH, 23 which is generally a characteristic of patients with classical primary aldosteronism but not of patients with low-renin hypertension. 17 But, although there are some suggestions that these patients with abnormal suppression of one or more aldosterone determinations with Florinef have primary aldosteronism, we cannot rule out the possibility that an abnormality in suppression may not reflect enhanced aldosterone secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma potassium determinations were also somewhat suggestive that these patients had subtle primary aldosteronism in that most of these patients had borderline hypokalemia. In addition, some of these patients demonstrated an enhanced aldosterone response to ACTH, 23 which is generally a characteristic of patients with classical primary aldosteronism but not of patients with low-renin hypertension. 17 But, although there are some suggestions that these patients with abnormal suppression of one or more aldosterone determinations with Florinef have primary aldosteronism, we cannot rule out the possibility that an abnormality in suppression may not reflect enhanced aldosterone secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced dopaminergic inhibition of aldosterone secretion during sodium restriction may allow an increased response of aldosterone to administration of angiotensin II, while increased dopaminergic tone may decrease this response during sodium loading (Holland, Thomas, Brown et al 1983;Aguilera & Catt, 1984;Sowers, 1984). Although in-vitro evidence suggests that high concentrations of dopamine inhibit aldosterone production by zona glomerulosa cells (McKenna, Island, Nicholson & Liddle, 1979), until recently there has been little direct evidence in normal man to support such a role for dopamine (Carey, Thorner & Ortt, 1979;Carey, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…[32]. Metoclopramide also evokes increased aldosterone secretion in the patients with primary aldosteronism caused by an adrenal adenoma or bilateral adrenal hyperplasia, again without any apparent involvement of known factors [29,[33][34][35][36]. Curiously, in the dexamethasone pretreated patients with glucocorticoid-suppressible aldosteronism metoclopramide fails to elicit a plasma aldosterone response [36] [48][49][50].…”
mentioning
confidence: 99%
“…Curiously, in the dexamethasone pretreated patients with glucocorticoid-suppressible aldosteronism metoclopramide fails to elicit a plasma aldosterone response [36] [48][49][50]. Limited studies in the patients with primary aldosteronism showed the results of bromocriptine treatment on the basal or stimulated plasma aldosterone concentration also to be variable [34,48,51,521. The relevance of these findings to the physiology or pathophysiology of aldosterone secretion is unclear.…”
mentioning
confidence: 99%